2015
DOI: 10.2147/jbm.s90078
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic considerations in idiopathic hypereosinophilia with warm autoimmune hemolytic anemia

Abstract: Hypereosinophilic syndrome (HES) encompasses numerous diverse conditions resulting in peripheral hypereosinophilia that cannot be explained by hypersensitivity, infection, or atopy and that is not associated with known systemic diseases with specific organ involvement. HES is often attributed to neoplastic or reactive causes, such as chronic eosinophilic leukemia, although a majority of cases remains unexplained and are considered idiopathic. Here, we review the current diagnosis and management of HES and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The findings of eosinophil in mural thrombus associated with acute coronary events like myocardial infarction, a condition associated with platelet aggregation further confirms the symbiotic association between the two [33]. The negative relationship between eosinophil count and the hematocrit in this study is in agreement with findings by Sweidan et al [18] who reported a case of autoimmune hemolytic anemia with Ibuprofen use. The pro-inflammatory features of eosinophils stimulate hemolysis, from disruption in membrane proteins, leading to altered cell cellular adhesion, increased permeability and osmotic fragility.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of eosinophil in mural thrombus associated with acute coronary events like myocardial infarction, a condition associated with platelet aggregation further confirms the symbiotic association between the two [33]. The negative relationship between eosinophil count and the hematocrit in this study is in agreement with findings by Sweidan et al [18] who reported a case of autoimmune hemolytic anemia with Ibuprofen use. The pro-inflammatory features of eosinophils stimulate hemolysis, from disruption in membrane proteins, leading to altered cell cellular adhesion, increased permeability and osmotic fragility.…”
Section: Discussionsupporting
confidence: 92%